Pengembangan Sistem Presensi Mahasiswa Elektronik Berbasis RFID - Raden Arief Setyawan (Fakultas Teknik, Universitas Brawijaya, 2015)
At the current Universita Brawijaya academic information system, recording of student attendance is still performed manually. After the lecture ended, operators must type it to input for academic data. This often led to human error, because there are a lot of data that must be entered in SIAKAD every day.Universitas Brawijaya has collaboration project with a state-owned bank as a student card provider. These cards have RFID facility. This study discusses the making of the automatic attendance system using RFID reader. This research include the design of RFID reader device, the communication SIAKAD system, and also also the analysis the possibility of system scalability. This sistem can handle simultaeous card reader tapping dince there are so many classes starting together throughout UB.The results showed that this system needs 3–23 seconds after the students start tapping the card to the reader to obtain all task and conclussion. Keywords: RFID Reader, Data Communication, Scalability architecture.